Dual pillars of agro-energy transition: Irrigation efficiency and corn waste pyrolysis-fermentation for sustainable ethanol production in Papua lowlands - Suyatno; Helen Riupassa; Marthina Mini; Rolling S. Gaspersz; Hendry Y. Nanlohy (Mechanical Engineering for Society and Industry, 2026)
Agricultural intensification in Indonesia increasingly relies on fossil energy inputs while leaving substantial agricultural residues underutilized. In Papua’s Keerom lowlands (<100 m altitude), maize expansion has created opportunities for integrating sustainable irrigation management with biomass-based energy systems. This study proposes a dual-pillar agro-energy framework combining irrigation efficiency analysis with pyrolysis–fermentation pathways for valorizing corn residues, particularly cobs and husks. Field survey data from 45 respondents were used to estimate energy inputs in maize cultivation, while pilot-scale pyrolysis experiments (450–550 °C) were conducted to evaluate biochar and bioenergy co-product generation. Results show that total energy input for corn production in Keerom averages 3,950 MJ ha⁻¹, substantially lower than values reported for mechanized highland systems. Slow pyrolysis produced approximately 27% biochar, 38% bio-oil, and 35% syngas, with biochar exhibiting a calorific value of 25.5 MJ kg⁻¹. Ethanol production through dilute acid hydrolysis and simultaneous saccharification fermentation yielded 28.3 L per 100 kg corn feedstock. The integrated system demonstrates potential for improving energy efficiency and reducing agricultural waste while generating decentralized renewable energy. These findings highlight the feasibility of circular agro-energy systems in tropical lowland environments and provide insights for sustainable biofuel development in eastern Indonesia.